MAKNA BUDAYA MANIK KE PIAN DALAM PENGASUHAN POSITIF PADA ANAK USIA DINI DI PAUH DESA KABUPATEN SINTANG. - Teodosia, Maria; R, Marmawi; Amalia, Annisa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to determine the meaning manik ke pian culture in positive parenting in early childhood in Pauh Desa, Sintang Regency. The meaning manik ke pian culture that you want to see here is the meaning of various kinds of activities contained in the implementation of manik ke pian culture and that parents can do when carrying out parenting during the implementation manik ke pian culture and also in the daily life of children. The type of research used in this study is qualitative research using ethnographic methods, and data collection through observation, interview and documentation activities. The subject in this study was the customary chief. Based on data analysis conducted by researchers, with the title of the meaning manik ke pian culture in positive parenting in early childhood in Pauh Desa, Sintang Regency, the results were obtained that the implementation of manik ke pian culture is an expression to ask God so that children can be purified from various bad things and the universe can accept children who live in the world by being bestowed with all blessings and sustenance. There are 3 series in the implementation manik ke pian cunture, namely afternoon begendang, morning begendang, and taking children to bathe down to the river.